2014
DOI: 10.1007/s11999-013-3022-7
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy Influences the Pseudocapsule Composition in Soft Tissue Sarcomas

Abstract: Background Soft tissue sarcomas are a heterogeneous group of malignant tumors. Standard treatment for soft tissue sarcoma of the extremity is surgical excision and adjuvant therapy; however, the role of neoadjuvant chemotherapy is controversial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 13 publications
(16 reference statements)
3
5
0
Order By: Relevance
“…In one European trial, adjuvant chemotherapy in the form of cyclophosphamide, vincristine, doxorubicin, and dacarbazine (CYVADIC) reduced local recurrence but not overall survival, similar to our study [4]. One theory regarding how chemotherapy might affect local control is that chemotherapy may affect actively dividing cells at the margins of tumors [19]. Although controversy remains regarding the topic with several articles failing to show an effect on local control [6,7,18], other studies have shown that chemotherapy could benefit patients with sarcoma in terms of better local relapse-free survival and overall survival [9,10,13,21].…”
Section: Discussionsupporting
confidence: 83%
“…In one European trial, adjuvant chemotherapy in the form of cyclophosphamide, vincristine, doxorubicin, and dacarbazine (CYVADIC) reduced local recurrence but not overall survival, similar to our study [4]. One theory regarding how chemotherapy might affect local control is that chemotherapy may affect actively dividing cells at the margins of tumors [19]. Although controversy remains regarding the topic with several articles failing to show an effect on local control [6,7,18], other studies have shown that chemotherapy could benefit patients with sarcoma in terms of better local relapse-free survival and overall survival [9,10,13,21].…”
Section: Discussionsupporting
confidence: 83%
“…Peritumoral PC is a layer of fibrous connective tissue surrounding the cancer. A complete PC can prevent tumor cells from infiltrating adjacent renal parenchyma and facilitate the smooth implementation of TE surgery (9). In contrast, patients with disrupted PC or infiltrated parenchyma are recommended to receive standardized NSS to avoid positive surgical margin.…”
Section: Original Articlementioning
confidence: 99%
“…The local recurrence of marginally excised subcutaneous STSs is variable and difficult to predict. STSs are commonly surrounded by a pseudo capsule that may contain or be confluent with tumor cells [ 30 ]. The resemblance to complete margins [ 31 , 32 ] does not predict recurrence.…”
Section: Discussionmentioning
confidence: 99%